PENERAPAN PRINSIP-PRINSIP HUKUM PERIKATAN DALAM PEMBUATAN KONTRAK (UINSI Samarinda, 2015)
Parties involved in making a contract should understand and be aware of conditions negotiated during the contract making. This is instrumental in order to anticipate disputes that may arise from such contract. When there are disputes in the future, thus, a party may seek remedies of his/her rights that have been injured by another party. This article discusses principles of contract law in Indonesia and its application in the contract making.